Upaya Revitalisasi Identitas Petani Lokal melalui Festival Mbok Sri Mulih (Studi Kasus Festival Mbok Sri Mulih di Desa Delanggu, Klaten) - Najikhatur Rojabiyah; Ghufronudin Ghufronudin; Yosafat Hermawan Trinugraha (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2023)
This research was conducted to know the efforts made by the Sanggar Rojolele together with the local farming community in revitalizing the identity of local farmers through holding the Mbok Sri Mulih Festival. This qualitative research used a case study approach was conducted in Delanggu Village, Klaten as a producer of Rojolele rice as well as a farmer who is attached to tradition through the Mbok Sri Mulih Festival. Informants in this study were selected through a purposive sampling method. The data obtained were collected through non-participatory observation, in-depth interviews, and documentation studies. The validity of the data has been tested through triangulation of sources to be further analyzed using an interactive model. Through this research, it can be seen that the revitalization effort is carried out through several stages there are the preservation or protection stage, the development stage, maintaining sustainability, and the creative process. The preservation or protection stage is realized through holding meetings with several parties to raise awareness of the importance of maintaining the identity of local farmers and discussing plans for implementing the Mbok Sri Mulih Festival activities. Followed by the development stage, namely by developing ideas and updating the festival program with various adjustments every year, as well as collaborating with several parties outside the Delanggu Village community. The stage of maintaining sustainability is carried out through the follow-up programs of the Sanggar Rojolele after the festival activities are carried out. The creative process is carried out through the development of ideas that have been discussed together and the direct involvement of local farming communities in enlivening the running of the Mbok Sri Mulih Festival.